1993
DOI: 10.1139/e93-215
|View full text |Cite
|
Sign up to set email alerts
|

The Dog Bay Line: a major Silurian tectonic boundary in northeast Newfoundland

Abstract: The Dog Bay Line separates different Silurian rock groups in northeast Newfoundland. West of the line, terrestrial volcanic rocks and sandstones (Botwood Group) overlie marine greywackes and conglomerates (Badger Group). East of the line, red sandstones overlie shallow marine shales and limestones (Indian Islands Group). Throughout Dog Bay, the line is marked by a disrupted zone of dark grey to black shales, volcanic rocks, and gabbros. Pervasive dextral, transpressive ductile deformation followed by successiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 0 publications
0
41
0
Order By: Relevance
“…The Tetagouche -Exploits back-arc basin was closed during Early Silurian time, once again bringing the various fragments of Ganderia back together (440 -430 Ma;van Staal 1994;van Staal et al 2003;Pollock et al 2007). The associated principal suture in Newfoundland is the Dog Bay Line (Williams et al 1993;van Staal et al 2009van Staal et al , 2014.…”
Section: Geological Settingmentioning
confidence: 99%
“…The Tetagouche -Exploits back-arc basin was closed during Early Silurian time, once again bringing the various fragments of Ganderia back together (440 -430 Ma;van Staal 1994;van Staal et al 2003;Pollock et al 2007). The associated principal suture in Newfoundland is the Dog Bay Line (Williams et al 1993;van Staal et al 2009van Staal et al , 2014.…”
Section: Geological Settingmentioning
confidence: 99%
“…1) are underlain by Paleozoic and older rocks of the Dunnage and Gander tectonostratigraphic zones (Williams 1978). Tectonostratigraphic zones and subzones were principally defined on their pre-Silurian geological characteristics, although it was later shown that geological contrasts locally continued into the Silurian (Williams et al 1988(Williams et al , 1993Reusch and van Staal 2012). The Dunnage zone mainly comprises Cambro-Ordovician arc terranes and associated slivers of supra-subduction zone ophiolites, which were divided into the Notre Dame subzone (periLaurentian realm) and the Exploits subzone (peri-Gondwanan realm), separated by the Red Indian Line (Williams et al 1988;Williams 1993b;Hibbard et al 2006Hibbard et al , 2007.…”
Section: Middle Ordovician-late Silurian Geological Architecture Of Tmentioning
confidence: 99%
“…2;Dunning and O'Brien 1989;van Staal 1994;Fyffe et al 2009; (van Staal 1994;van Staal et al 1998). Contrasts in the Ordovician-Silurian geology led to an additional subdivision of the Exploits subzone by Williams et al (1993), and introduction of the Dog Bay Line (Fig. 1).…”
Section: Middle Ordovician-late Silurian Geological Architecture Of Tmentioning
confidence: 99%
See 1 more Smart Citation
“…19B). van Staal et al (1998van Staal et al ( , 2009 interpreted this margin as the back-arc side, and thought that opening of the Tetagouche ocean, splitting the older (now inactive) Penobscot Arc into two parts, starting ~475 Ma, requires this margin not to have become the site of subduction until late Ordovician-early Silurian time, and that subduction ended in the later Silurian by collision of the Exploits subzone with the Ganderia margin (van Staal et al 1998(van Staal et al , 2009, the suture represented now (Williams et al 1993;S.H. Williams et al 1995) by the Dog Bay Line.…”
Section: Regional Implicationsmentioning
confidence: 99%